Toxicity evaluation of standardized and nanoliposomal extracts of Labisia pumila whole plant (Blume, Myrsinaceae) in Sprague Dawley rats - Ahmed Saeed, Mohammed Ali; Memon, Abdul Hakeem; Hamil, Mohd Shahrul Ridzuan; Hooi, Kheng Beh; Mohammed Saghir, Sultan Ayesh; Kaur, Gurjeet; Sadikun, Amirin; Ismail, Zhari (2018)
Purpose: To investigate the toxicity of Labisia pumila standardized extract (LPE) and its liposomal extract (LLP). Methods: For acute toxicity study, LPE or LLP was orally administered (2000 mg/kg) in single doses to Sprague Dawley rats and the routine activity of the rats was continuously monitored for a total of 14 days. After 14 days of treatment, all rats were sacrificed and their vital organs were excised, weighed and macroscopically examined, while for a repeated dose toxicity study, the rats were orally administered with LPE or LLP at the selected doses (250, 500 and 1000 mg/kg) for a period of 28 days. The animals were sacrificed (anaesthetized by sodium pentobarbitone and blood was collected by cardiac puncture), followed by examination of their body organs and blood serum. Results: LPE and LLP at 2000 mg/kg did not produce mortality or significant changes in the general behaviour, body weight and organ gross appearance of the rats. In repeated dose toxicity study no significant changes in, growth, organ weights, haematological parameters, biochemical values and histological features of vital organs of the treated groups, compared to the control group. Conclusion: The no-adverse-effect-level for LPE and LLP is (1000 mg/kg/day) when administered orally for 28 days.